Evidence-based interventions for reading and language difficulties: Creating a virtuous circle - Snowling, M; Hulme, C (2011)
Background: Children may experience two very different forms of reading problem: decoding difficulties (dyslexia) and reading comprehension difficulties. Decoding difficulties appear to be caused by problems with phonological (speech sound) processing. Reading comprehension difficulties in contrast appear to be caused by problems with 'higher level' language difficulties including problems with semantics (including deficient knowledge of word meanings) and grammar (knowledge of morphology and syntax). Aims: We review evidence concerning the nature, causes of, and treatments for children's reading difficulties. We argue that any well-founded educational intervention must be based on a sound theory of the causes of a particular form of learning difficulty, which in turn must be based on an understanding of how a given skill is learned by typically developing children. Such theoretically motivated interventions should in turn be evaluated in randomized controlled trials (RCTs) to establish whether they are effective, and for whom. Results: There is now considerable evidence showing that phonologically based interventions are effective in ameliorating children's word level decoding difficulties, and a smaller evidence base showing that reading and oral language (OL) comprehension difficulties can be ameliorated by suitable interventions to boost vocabulary and broader OL skills. Conclusions: The process of developing theories about the origins of children's educational difficulties and evaluating theoretically motivated treatments in RCTs, produces a 'virtuous circle' whereby theory informs practice, and the evaluation of effective interventions in turn feeds back to inform and refine theories about the nature and causes of children's reading and language difficulties. ©2010 The British Psychological Society.